Analysis of Production and Income of Live Shrimp Fishermen after Kendari Bay Revitalization - Manakarra, Yulia Citra; Muhammad Aswar Limi; Samsul Alam Fyka (International Journal of Technology and Education Research, 2024)
The results of this research aim to: (1) Find out how much production and income earned by live shrimp fishermen after the revitalization of Kendari Bay. (2) Knowing the feasibility of the live shrimp fishing business after the revitalization of Kendari Bay. This research was carried out in March 2024 in Lahundape Village. The population in the study, namely fishermen who run a live shrimp business, numbered 8 people, using a broad sampling technique where all members were sampled as the research sample. The analysis used is analysis of costs, revenues, income and R/C Ratio obtained from research results which show that shrimp production after the revitalization of Kendari Bay is 18 kg/month with an average total cost of Rp. 287,590, the total average receipt is Rp. 2,700,000, the average total income of Rp. 2,412,410 and the R/C ratio for live shrimp fishermen is 9.4. This ratio meets business feasibility standards because the R/C Ratio is >1, meaning every Rp. 1 fee will get 9.4 times revenue